The relationship between dysbiosis and the development of neurodegenerative disorders: a systematic literature review - Vilanova, Juliana de Castro; Melo, Beatriz Ribas de; Rocha, Thaiz Helena Lopes da; Rocha, Iane Lopes da; Guerra, Bruno Mendes Moura Dias; Garcês, Tereza Cristina Carvalho de Sousa; Andrade, Ana Rachel Oliveira de (Research, Society and Development, 2023)
Dysbiosis consists of an imbalance between protective and aggressive bacteria in the gastrointestinal tract (GI tract), associated with the production of toxins that can be harmful to health. The impact on the intestinal microbiome can be caused by the indiscriminate use of medications, inadequate diet, immunological disorders, and advancing age. The present work aims to analyze, by comparing 23 studies, how the gut-brain axis is influenced by gastrointestinal bacteria and their modifications when dysbiotic, as well as their participation in the development of neurodegenerative diseases such as Alzheimer's disease (AD), Amyotrophic lateral sclerosis (ALS), and Parkinson's disease (PD) - and to list the advantages of therapies to optimize the prognosis of these diseases. As for AD, the gut microbiota may influence its onset and/or progression, through increased amyloid-beta immunoreactivity and phospho-tau changes; moreover, bacterial secretions stimulate neuroinflammation and neurodegeneration. In ALS, the reduction of bacteroid groups promotes increased abundance of cyanobacteria producing neurotoxic molecules. Regarding PD, studies state that the disease may begin in the intestine through correlation with alpha-synuclein aggregation in the colon. As for therapy, researchers state that dietary modifications and the use of antibiotics and probiotics help rescue the intestinal microbiome and reduce neurodegeneration; it is also highlighted that fecal matter transplantation is neuroprotective by reducing intestinal dysbiosis. It is concluded that neurodegenerative diseases are stimulated by the product of bacteria, which affect the blood-brain barrier and negatively influence the homeostasis of the nervous system.